Surgical Decision Making From Image-Based Biophysical Modeling of Glioblastoma: Not Ready for Primetime. Issue 5 (6th April 2017) - Amelot, Aymeric; Deroulers, Christophe; Badoual, Mathilde; Polivka, Marc; Adle-Biassette, Homa; Houdart, Emmanuel; Carpentier, Antoine F.; Froelich, Sebastien; Mandonnet, Emmanuel
Abstract: BACKGROUND: Biophysical modeling of glioma is gaining more interest for clinical practice. The most popular model describes aggressivity of tumor cells by two parameters: net proliferation rate (ρ) and propensity to migrate (D). The ratio ρ/D, which can be estimated from a single preoperative magnetic resonance imaging (MRI), characterizes tumor invasiveness profile (high ρ/D: nodular; low ρ/D: diffuse). A recent study reported, from a large series of glioblastoma multiforme (GBM) patients, that gross total resection (GTR) would improve survival only in patients with nodular tumors. OBJECTIVE: To replicate these results, that is to verify that benefit of GTR would be only observed for nodular tumors. METHODS: Between 2005 and 2012, we considered 234 GBM patients with pre- and postoperative MRI. Stereotactic biopsy (BST) was performed in 109 patients. Extent of resection was assessed on postoperative MRI and classified as GTR or partial resection (PR). Invasiveness ρ/D was estimated from the preoperative tumor volumes on T1-Gadolinium-enhanced and fluid-attenuated inversion recovery sequences. RESULTS: We demonstrate that patients with diffuse GBM (low ρ/D), as well as more nodular (mid and high ρ/D) GBM, presented significant survival benefit from GTR over PR/BST ( P < .001). CONCLUSION: Whatever the degree of tumor invasiveness, as estimated from MRI-driven biophysical modeling, GTR improves survival of GBM patients, compared to PR or BST. This conflicting result should motivate further studies.